Historiography and source base development of metrological support in Ukraine (ХХ – beginning of ХХІ centuries) - I. Yu. Lyashuga (History of science and technology, 2018)
The article is devoted to the determination of the state of scientific elaboration of the problem of forming the system of metrological support in Ukraine during the 20th century - the beginning of the XXI century. The system of metrological support is scientific and organizational bases in combination with technical means, norms and rules is an effective means of achieving the necessary accuracy and quality of measurements in all spheres. During the ХХ century a network of research institutes in the field of metrology has been formed in Ukraine and a number of standards have been created. The most fruitful for the development of the reference base was the period of 1991 – the beginning of the XXI century. Despite a certain amount of scientific literature on metrology and metrological support, the process of deploying research and development of metrology in Ukraine during the ХХ century – beginning of the XXI century not received proper coverage in the historical literature. A classification of the main directions of research problems by subject-thematic basis. It is proved that the first chronological stage of historiography of the selected problem (1900 – the beginning of the twentieth century) was characterized by a small amount of scientific literature on the history of the formation and development of metrological support in Ukraine. The second stage, which began at the turn of 1917 – 1991, was observed a revival of interest in publications on the history of metrology, but the overwhelming majority of them are developments of an anniversary character. At three at the stage (after 1991), scientific works appeared directly devoted to the development of metrological support and the formation of a technical regulation system and the creation of standards in Ukraine. The initial bases of the problem under study are analyzed, the classification of attracted sources is carried out, their information potential is determined. As a result of processing a number of sources from the central and regional archives of Ukraine, a historical reconstruction of the formation of the system of the metrological service of Ukraine during 1901 – 1991 was carried out. As a result of the analysis of the well-known and little-known works of metrologists, museum collections, the article highlights the problem of creating a unique national reference Base Ukraine at the end of the ХХ – beginning of ХХІ centuries. The involvement of the current paperwork of the scientific departments of the NSC “Institute of Metrology”, educational institutions, patent statistical information made it possible to more accurately clarify the reorganization processes that occurred in the context of globalization of the world economy in the sphere of standardization and conformity assessment and integration of Ukraine into the world economy. A number of personal documents are brought to the source base, namely: autobiography, memoirs, correspondence, interview materials.